2014
DOI: 10.1097/mcc.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic evaluation of the heart

Abstract: Echocardiography has now become an important tool for hemodynamic evaluation of the critically ill patient. Echocardiography should be performed in most patients with circulatory and respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…A valid tool to access diastolic and systolic function and hemodynamics in septic and critically ill patients is provided by echocardiography [48]. Echocardiographic evaluation of septic mice was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…A valid tool to access diastolic and systolic function and hemodynamics in septic and critically ill patients is provided by echocardiography [48]. Echocardiographic evaluation of septic mice was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, improvement in monitoring has allowed for a better adjustment of the therapy, minimizing the hazards of both over and under-treatment. Methods of non-invasive cardiac output monitoring, such as echocardiography and ultrasonic cardiac output monitor (USCOM) are available bedside and have their use incorporated in many intensive care units worldwide (17,18). Improvement in microcirculatory monitoring has revealed that profound derangements may be present in septic patients; timely reversal of these abnormalities impacts positively on the outcomes (19).…”
Section: Adequate Hemodynamic Resuscitation Is Not Enough For Survivalmentioning
confidence: 99%
“…In patients, the intention is to obtain these images transesophageally or transthoracally, which are established methods in humans (Poelaert et al. ; De Backer ).…”
Section: Discussionmentioning
confidence: 99%
“…Doppler signals from the ascending aorta were in this study obtained by placing the GE 6T probe directly on the apex of the heart, as we had difficulties obtaining satisfactory images from a transesophageal position in the pigs. In patients, the intention is to obtain these images transesophageally or transthoracally, which are established methods in humans (Poelaert et al 1999;De Backer 2014).…”
Section: Limitations Of the Studymentioning
confidence: 99%